Leadership in sport - study with futsal coaches in “under 17” and senior levels - Honório, Samuel (2018)
Introduction: The leader, in the coach role, must be able to relate and establish connections with his athletes, and contribute to the construction of an environment conducted by fair and clear norms that do not oppose the organizational culture of the club (Lopes, 2008; Mendo & Ortiz, 2003). Objective: The objective of this research was to identify the leadership behaviours of two coaches from different levels (Under 17 and Seniors), as well as the perception of leadership behaviours of their players. Methodology: The sample consisted of two coaches and 26 players, 12 of them in the “Under 17” level aged between 15 and 17 years, and 14 senior players, aged between 18 and 33 years. We used the Leadership Scale for Sports (LSS) / Leadership Scale in Sport, by Chelladurai & Saleh (1978). In this descriptive and inferential study, the Kolmogrov-Smirnov test was performed for the normality assumptions by choosing the parametric statistic and to analyse the differences between the variables, a Student-T test was performed. Five dimensions were analysed: Training Instruction, Social Support, Reinforcement, Democratic Behaviour and Autocratic Behaviour. The results obtained showed significant differences between the coach's self-perception and the players' perception, as well as their preferences and their comparison between levels. According to coaches, the dimension of training instruction and reinforcement, are the styles of leadership with more emphasis and the smaller is the autocratic.